1,3‐Bis(aryloxy)propan‐2‐ols as potential antileishmanial agents - Lavorato, Stefânia N. (Chem Biol Drug Des, 2017)
We describe herein the synthesis and antileishmanial activity of 1,3‐bis(aryloxy)propan‐2‐ols. Five compounds (2, 3, 13, 17, and 18) exhibited an effective antileishmanial activity against stationary promastigote forms of Leishmania amazonensis (IC (50) < 15.0 μm), and an influence of compound lipophilicity on activity was suggested. Most of the compounds were poorly selective, as they showed toxicity toward murine macrophages, except 17 and 18, which presented good selective indexes (SI ≥ 10.0). The five more active compounds (2, 3, 13, 17, and 18) were selected for the treatment of infected macrophages, and all of them were able to reduce the number of internalized parasites by more than 80%, as well as the number of infected macrophages by more than 70% in at least one of the tested concentrations. Altogether, these results demonstrate the potential of these compounds as new hits of antileishmanial agents and open future possibilities for them to be tested in in vivo studies.